2018
DOI: 10.1074/jbc.ra117.001627
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of bi- and trispecific antibodies targeting multiple filovirus glycoproteins

Abstract: Filoviruses (family Filoviridae) include five ebolaviruses and Marburg virus. These pathogens cause a rapidly progressing and severe viral disease with high mortality rates (generally 30-90%). Outbreaks of filovirus disease are sporadic and, until recently, were limited to less than 500 cases. However, the 2013-2016 epidemic in western Africa, caused by Ebola virus (EBOV), illustrated the potential of filovirus outbreaks to escalate to a much larger scale (over 28,000 suspected cases). mAbs against the envelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In general, the filovirus field is moving toward the development of pan-ebolavirus or even pan-filovirus mAb cocktails. Several studies have described mAbs with in vitro and in vivo efficacies against multiple ebolavirus species [10][11][12][13][14]. Human data have even shown that cross-protection for EBOV and MARV can be naturally achieved [15], further supporting the pan-filovirus therapeutic concept.…”
Section: Resultsmentioning
confidence: 97%
“…In general, the filovirus field is moving toward the development of pan-ebolavirus or even pan-filovirus mAb cocktails. Several studies have described mAbs with in vitro and in vivo efficacies against multiple ebolavirus species [10][11][12][13][14]. Human data have even shown that cross-protection for EBOV and MARV can be naturally achieved [15], further supporting the pan-filovirus therapeutic concept.…”
Section: Resultsmentioning
confidence: 97%
“…Multispecific antibodies with enhanced antiviral breadth and cross-protective efficacy have also been engineered and evaluated in rodent models of filovirus challenge. nAbs specific for different ebolaviruses and MARV were successfully combined into broadly neutralizing bispecific and trispecific antibodies ( 63 , 64 ). In the distinct Trojan horse approach, bsAbs were generated by linking a pan-ebolavirus non-neutralizing mAb, FVM09, with either of two mAbs targeting cryptic endosomal epitopes at the GP CL :NPC1 interface ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAb therapies that target two or more epitopes are advantageous for viral immunotherapy, because they are less susceptible to viral escape by a single mutation. Such multi-epitope targeting can be accomplished either by mixing canonical mAbs together into cocktails (e.g., Inmazeb or MBP134) or by physically joining variable domains (Fvs) from two antibodies as bispecific (bsAbs) or multispecific (e.g., trispecific) antibodies [32,33]. We have previously reported the development of bsAbs against filoviruses, and Crimean-Congo hemorrhagic fever virus (CCHFV), and other groups have targeted SARS-CoV-2 and HIV-1 [32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%